2020
DOI: 10.1016/j.numecd.2019.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the echocardiographic assessment of epicardial adipose tissue thickness at the Rindfleisch fold for the prediction of coronary artery disease

Abstract: Background and Aim: Echocardiography is a promising technique for the assessment of epicardial adipose tissue (EAT). Increased EAT thickness is associated with different cardiac diseases, including; coronary artery disease (CAD). Since several different echocardiographic approaches have been proposed to measure EAT, the identification of a standardized method is needed. We propose the assessment of EAT maximal thickness at the Rindfleisch fold, the reproducibility of this measurement and its correlation with E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 25 publications
0
28
2
Order By: Relevance
“…However, echocardiography is certainly the more simple and diffuse methodology, available in the acute settings. We previously validated the echocardiographic method for EAT thickness determination used in the present study against CMR and we reported an excellent intra and inter observer variability in CAD patients (Parisi et al, 2020c).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…However, echocardiography is certainly the more simple and diffuse methodology, available in the acute settings. We previously validated the echocardiographic method for EAT thickness determination used in the present study against CMR and we reported an excellent intra and inter observer variability in CAD patients (Parisi et al, 2020c).…”
Section: Discussionmentioning
confidence: 66%
“…In this prospective study conducted on STEMI patients we evaluated changes in EAT thickness, measured at the Rindfleisch fold (Parisi et al, 2020c), at baseline and at 3 months after the event. The presence of a standardized protocol for the management of STEMI and the strictly inclusion and exclusion criteria allowed us to study in a homogeneous population both myocardial and inflammatory remodeling after the injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EAT was visualized in parasternal long-axis view between the free wall of the right ventricle and the anterior surface of the ascending aorta. Once visualized the EAT deposit, the maximum EAT thickness was measured at end-systole, as we have previously described (Parisi et al, 2019b). The average value from three cardiac cycles was used for the statistical analysis.…”
Section: Study Populationmentioning
confidence: 99%